Periodontite e síndrome metabólica: existe associação? - Merces, Magno Conceição das (2014)
Introduction: Metabolic syndrome (MS ) has aroused interest in the health field, it is seen as the major factor for the occurrence of cardiovascular events . Causal factors associated with metabolic syndrome are not well defined and many unidentified. Still preliminary investigations suggest that infections may be involved in the causal chain of this syndrome. This study aimed to estimate the association between periodontal infection, presence of periodontitis and the diagnosis of metabolic syndrome. Methods: A cross-sectional study was conducted with 419 participants. After application of a questionnaire, general and oral clinical examination and data collection laboratory test, the diagnosis of periodontitis and metabolic syndrome were performed. The magnitude of the association between periodontitis and diagnosis of metabolic syndrome was expressed by the prevalence ratio (PR) and a confidence interval of 95 % ( 95 % CI ). The analysis of the effect of periodontitis on metabolic syndrome the multivariate Poisson regression with robust variance was applied. Results: The findings of this study were presented in a paper to be published in the Journal of Periodontology. There was no association between periodontitis and metabolic syndrome in two models of analysis performed according to the diagnosis of the syndrome, RPajustada1 = 1.01, 95% CI [ 0.75 to 1.34 ] , p = 0.97 and RPajustada2 = 0 95 , 95% CI [ 0.72 to 1.26 ] , p = 0.74 , even after adjusting for sex, age, education level, and smoking. Conclusions: periodontitis was not an independent factor for SM.